Influência do fogo na estrutura e dinâmica da vegetação arbustiva-arbórea em mancha de savana isolada na Amazônia Oriental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Fire has caused changes in the populations and communities of savannas in Alter do Chão, through direct or indirect effects. However, it is not yet clear how the shrub-tree vegetation is affected, because monitoring studies had not been carried out until then. The objective of this study was to evaluate the structure of the shrub-tree vegetation submitted to different fire regimes in an isolated Amazon Savannah in Alter do Chão - PA. Simultaneously, to analyze the variations that occurred in this vegetation in the interval of ten years, considering the fire as main agent of change. The study area is located between the city of Santarém and the district of Alter do Chão, in the State of Pará. In 2008, two permanent plots of 1 ha each (100 x 100 m) were located in areas with defined as Savana with fire (SCF) and Savana without fire (SSF). A floristic inventory was carried out of the shrub-arboreal individuals with diameter at 1.30 cm of soil (DBH) ≥ 10 cm, and these plots were evaluated again in 2018 for analysis of vegetation dynamics. Another 12 rectangular plots of 10 x 250 m (0.25 ha) were installed and all shrub-tree individuals with height from 2 meters and diameter to 30 cm from the soil (D30) from 5 cm were measured. In each of these plots, an area of 1 m x 250 m was delineated, where individuals with 5 cm <D30 ≥ 2 cm were sampled. The main result was that the fire regime significantly influenced the current structure of the shrub-tree vegetation, reducing the density and basal area of the individuals. It can be said that 45% of the current density and 44% of the basal area are explained by the number of fires occurred. The species diversity was different between the analyzed areas and between the evaluated periods, but was generally smaller for SCF and larger for SSF. The density and basal area were higher in SSF than in SCF in both evaluated periods. Mortality rates exceeded recruitment rates in the Alter do Chão savannah in both SCF and SSF, which resulted in a negative balance between these rates. This imbalance did not interfere with the occurrence of species with high density and good survival, which were able to stand out and dominate the environment. In 2008, the species Salvertia convallariodora, Himatanthus drasticus, Anacardium occidentale, Byrsonima crassifolia and Vatairea macrocarpa were the most important species, while in SSF the species Salvertia convallariodora, Qualea grandiflora, Pouteria ramiflora, Byrsonima crassifolia and Handroanthus sp. were the most important. In 2018, the species Salvertia convallariodora, Himatanthus drasticus, Anacardium occidentale, Byrsonima crassifolia and Byrsonima coccolobifolia were the most important species, while the species Salvertia convallariodora, Qualea grandiflora, Pouteria ramiflora, Byrsonima crassifolia, Tachigali vulgaris, Himatanthus drasticus, Xylopia aromatica and Simarouba amara were the most important. Considering the structure observed in SCF and SSF in 2008, despite the changes, the studied communities showed high stability, maintaining their structure and diversity of species over time.
Keywords: Alter-do-Chão (PA); Mudanças estruturais; Fitossociologia; Incêndios; CNPQ::CIÊNCIAS BIOLÓGICAS